Disaster Management: Towards Building Community Resilience - Matunhay, Lilybeth Musong (International Journal of Scientific Research and Management (IJSRM), 2018)
Climate change is one of the major challenges faced by countries worldwide. In the Philippines, constant typhoons and flooding have exposed the vulnerability of disaster risk and reduction management of local communities, and such untold miseries increased the loss and damages of human lives and economic assets. While project management approach has been effectively applied to many fields and sectors, disaster management has yet to see its full benefits. Data from the Office of the Department of Interior and Local Government (DILG) revealed that in 2014, the Municipality of Compostela had been awarded the “Seal of Good Local Governance on Disaster Preparedness” (SGLG). Thus, this captures the interest of the researcher to determine indicators of the local government unit’s disaster management that predict disaster resiliency to the major natural disasters occurring in the Municipality of Compostela for the last five years which include flooding and typhoon. This study employed a descriptive correlation design as the overall scheme in the conduct of the study. Specifically, Regression Analysis was utilized using disaster resiliency as the outcome variable and disaster management in terms of leadership structure, a guide to action management and partnerships and volunteerism as predictors. Results reveal that risk assessment and mapping,   partnerships with volunteer groups, civil society organizations (CSO) and business/private sectors, institutionalized planning and budgeting and functional incident command system significantly influence LGU’s resiliency towards flooding while partnerships with volunteer groups, CSO and business/private sectors, partnerships with other local governments and national government, institutionalized planning and budgeting and risk assessment and mapping significantly influence LGU’s resiliency towards typhoon.